Gender Communication Patterns in Broken Home Families - Jusnawati Jusnawati; Salwia Salwia; Siswanto Rawali (Universitas Lambung Mangkurat, 2025)
Gender communication plays an important role in shaping the dynamics of interaction in families, especially in broken home families. This study aims to analyze the role of gender in gender communication patterns of broken home families in Pampangan hamlet, A'bulosibatang village, Marusu sub-district. The research method used is a qualitative approach with in-depth interview techniques and observation of family members who experience parental separation. The results of the study indicate that the communication pattern applied is a balanced split pattern. Where communication in the family is divided equally, but family members tend to side with one parent. Children still have good communication relationships with both parents,s but are closer to one of them. Children who are raised by mothers tend to experience more emotional and open communication, while children who are raised by fathers more often experience instructional, limited, and less expressive communication. So that a mother only elaborates the feminine aspect more in communicating with her children, both girls and boys. Likewise, a father who is more dominant in actualizing the masculine aspect in interacting with children affects the development of the children who live with him. Communication patterns in broken home families in this area are still influenced by the dominant gender construction in society. Therefore, a more inclusive and supportive communication approach is needed to help family members deal with the emotional and social challenges resulting from parental separation